Ikigai and Urip iku Urub: A Comparative Study of Japanese and Javanese Philosophy - Purwandaru, R. Arief Toto; Suhartini (Universitas Negeri Yogyakarta, 2026)
Background: Japanese and Javanese are two languages rich in philosophy. One of the most prominent Japanese philosophies is